KAJIAN TEORITIS PENANGGULANGAN PENYALAHGUNAAN NARKOTIKA - SATRIANA, I MADE WAHYU CHANDRA (Kerta Dyatmika, 2015)
ABSTRACTÂ Act No. 35 Year 2009 on Narcotics is a rule that can not be separated from the purpose of the Act, namely to prevent drug abuse and combat illicit trafficking. Law enforcement in order to tackle the abuse of drugs is not enough to implement the law and carry out the proceedings in criminal justice with criminal sanctions (strafsoort) prison, because it felt less effective in law enforcement in Indonesia.In law enforcement would be difficult to seek justice if between law and morals are separated. Moral principles contained in the law is not an agreement on law enforcement alone, but because of the principle - the principle of morality is correct. Law enforcement should be directed to the protection of the public from crime, as well as the balance and harmony of life in society. Rule shared between the Chairman of the Supreme Court, Minister of Justice and Human Rights, the Minister of Health, Minister of Social Affairs, the Attorney General, Chief of Police, and the head of BNN RI, agreed that for users and drug addicts rehabilitation pursued social and medical rehabilitation.Â Keywords: Narcotics Abuse, RehabilitationÂ